Ecological remarks and re-description of the hermit crab-associated pleustid amphipod Pleusymtes japonica (Gurjanova, 1938) (Crustacea: Amphipoda: Pleustidae: Pleusymtinae) from the Russian coasts of the Sea of Japan - Ivan, Marin; Sergey, Sinelnikov; Agniya, Sokolova (Zootaxa, 2013)
Numerous specimens of poorly known pleustid amphipod Pleusymtes japonica (Gurjanova, 1938) (Crustacea: Amphipo-da: Pleustidae: Pleusymtinae) were found in association with large hermit crab Pagurus ochotensis Brandt, 1851 (Crustacea: Decapoda: Paguridae) near Furugelma Island in the Sea of Japan. This is the first report of the species in association with hermit crabs. Amphipods were found living close to the shell aperture and hermit crab feeding append-ages. Color photographs, remarks on ecology and re-description of the species are given.